PIWIL1 interacting RNA piR-017724 inhibits proliferation, invasion, and migration, and inhibits the development of HCC by silencing PLIN3 - Wu, Yi-Jing; Wang, Jie; Zhang, Peng; Yuan, Liu-Xia; Ju, Lin-Ling; Wang, Hui-Xuan; Chen, Lin; Cao, Ya-Li; Cai, Wei-Hua; Ni, Yi; Li, Min (Frontiers in Oncology, 2023)
Background Hepatocellular carcinoma (HCC) accounts for the majority of primary liver cancers. Worldwide, liver cancer is the fourth most common cause of cancer-related death. Recent studies have found that PIWI-interacting RNAs (piRNAs) participate in the occurrence and development of various tumors and are closely related to the growth, invasion, metastasis and prognosis of malignant tumors. Studies on the role and functional mechanism of piRNAs in HCC development and progression are limited. Methods Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) were used to detect the expression of piR-017724 in both HCC tissues and cells. Based on the clinical data of HCC patients, the clinical and prognostic value of piR-017724 was further analyzed. Then, targeted silencing and overexpressing of piR-017724 in HCC cells was further used to examine the biological functions of piR-017724. In addition, the downstream target protein of piR-017724 was predicted and validated through high-throughput sequencing and public databases. Results The piR-017724 was significantly downregulated in HCC tissues and cells, and the downregulation of piR-017724 was associated with tumor stage and poor prognosis in HCC. The piR-017724 inhibitor promoted the proliferation, migration and invasion of HCC cells, while the piR-017724 mimic had the opposite effect. However, the piR-017724 did not affect apoptosis of HCC cells. High-throughput sequencing and qRT-PCR confirmed a reciprocal relationship between piR-017724 and PLIN3. Therefore, we speculate that piR-017724 may inhibit the development and progression of HCC by affecting the downstream protein PLIN3. Conclusions Our study shows that piR-017724, which is lowly expressed in HCC, inhibits the proliferation, migration and invasion of HCC cells and may affect the development of hepatocellular liver cancer through PLIN3, which provides new insights into the clinical application of piR-017724 in the treatment of hepatocellular carcinoma.